What's in a Name? Health Literacy Leaders Say Plenty!. Issue 3 (3rd July 2017) - Kim, Jeesun; Lee, Youngah; Gardner, Liz; Park, Hyojung; Cameron, Glen T.
ABSTRACT: Analysis of 100 in-depth interviews with academic, clinical, educational, and administrative leaders in health literacy examined these experts' definitions of health literacy and explored emerging themes pertaining to the status and definition of the concept. Drawing on Nutbeam's (1999, 2000) trilevel model of health literacy and Shannon and Weaver's (1949) information model of communication, the authors propose a process model of health literacy comprising four primary factors: message (the health-related informational component); information-based action (individuals' understandings of and use of health information beyond simply receiving the information); communication tools (the channels by which individuals receive health information); and the health care system (an environment where health care is provided and performed). The health literacy experts interviewed in this study perceived most problems in the message and health care system components, followed by communication tools and action. These findings suggest the need for improved presentation of health information to health consumers, as well as more education to build critical literacy skills. More efforts should be made to shift the conceptual understanding of health literacy from a persistent focus on word and number literacy (i.e., functional literacy) to more interactive and critical components, such as patient-provider communication and cultural competence.